Oligonucleotide-based label-free detection with optical microresonators: strategies and challenges. Issue 14 (16th June 2016) - Toren, Pelin; Ozgur, Erol; Bayindir, Mehmet
Abstract : This review targets diversified oligonucleotide-based biodetection techniques, focusing on the use of microresonators of whispering gallery mode (WGM) type as optical biosensors mostly integrated with lab-on-a-chip systems. Abstract : This review targets diversified oligonucleotide-based biodetection techniques, focusing on the use of microresonators of whispering gallery mode (WGM) type as optical biosensors mostly integrated with lab-on-a-chip systems. On-chip and microfluidics combined devices along with optical microresonators provide rapid, robust, reproducible and multiplexed biodetection abilities in considerably small volumes. We present a detailed overview of the studies conducted so far, including biodetection of various oligonucleotide biomarkers as well as deoxyribonucleic acids (DNAs), ribonucleic acids (RNAs) and proteins. We particularly advert to chemical surface modifications for specific and selective biosensing.